Microbial contamination of contact lenses after scaling and root planing using ultrasonic scalers with and without protective eyewear: A clinical and microbiological study - Rooh Afzha; Anirban Chatterjee; Shobha Krishna Subbaiah; Avani Rangaraju Pradeep (Wolters Kluwer Medknow Publications, 2016)
Background: Ultrasonic scaler is a preferential treatment modality among the clinicians. However, the aerosol/splatter generated is a concern for patients and practitioners. Therefore, the purpose of this study was to evaluate contamination of contact lenses of the dentist after scaling and root planing using ultrasonic scalers with and without protective eyewear. Materials and Methods: Thirty patients were randomly selected for scaling and root planing and divided into 2 groups of 15 each. Group A - dentist wearing contact lenses and protective eyewear. Group B - dentist wearing only contact lenses. After scaling and root planing using ultrasonic scalers, the lenses were subjected to culture and 16S rRNA (16S ribosomal RNA) gene sequencing. Results: In Group A - 15 out of thirty samples were contaminated, in Group B - all the thirty samples were contaminated. Most of the samples showed Gram-positive bacteria and 5 samples were contaminated with fungi. 16S rRNA gene sequencing of forty contaminated samples showed that 31 were contaminated with Streptococcus mutans and 9 with Staphylococcus aureus. Conclusion: Keeping in mind the limitation of the study for the absence of negative control, we would like to conclude that dental practitioners should better avoid contact lenses in a dental setup because of the risk of contamination of the contact lenses from the various dental procedures which can produce aerosol/splatter and if worn, it is recommended to wear protective eyewear.